Air temperature, relative humidity, climate regionalization and thermal comfort of Nigeria - Eludoyin, Oyenike M.; Adelekan, Ibidun O.; Webster, R; Eludoyin, Adebayo O (International Journal of Climatology, 2023)
International Journal of Climatology, Issue no:May 2014, Pg.(1-19)